Complement receptor 2 is up regulated in the spinal cord following nerve root injury and modulates the spinal cord response. Issue 1 (December 2015) - Lindblom, Rickard; Berg, Alexander; Ström, Mikael; Aeinehband, Shahin; Dominguez, Cecilia; Al Nimer, Faiez; Abdelmagid, Nada; Heinig, Matthias; Zelano, Johan; Harnesk, Karin; Hübner, Norbert; Nilsson, Bo; et al.
Abstract Background Activation of the complement system has been implicated in both acute and chronic states of neurodegeneration. However, a detailed understanding of this complex network of interacting components is still lacking. Methods Large-scale global expression profiling in a rat F2(DAxPVG) intercross identified a strongcis -regulatory influence on the local expression of complement receptor 2 (Cr2) in the spinal cord after ventral root avulsion (VRA). Expression of Cr2 in the spinal cord was studied in a separate cohort of DA and PVG rats at different time-points after VRA, and also following sciatic nerve transection (SNT) in the same strains. Consequently, Cr2 −/− mice and Wt controls were used to further explore the role of Cr2 in the spinal cord following SNT. The in vivo experiments were complemented by astrocyte and microglia cell cultures. Results Expression of Cr2 in naïve spinal cord was low but strongly up regulated at 5–7 days after both VRA and SNT. Levels of Cr2 expression, as well as astrocyte activation, was higher in PVG rats than DA rats following both VRA and SNT. Subsequent in vitro studies proposed astrocytes as the main source of Cr2 expression. A functional role for Cr2 is suggested by the finding that transgenic mice lackingCr2 displayed increased loss of synaptic nerve terminals following nerve injury. We also detected increased levels of soluble CR2 (sCR2) in the cerebrospinal fluid of rats following VRA. Conclusions These results demonstrate that local expression of Cr2 in the central nervous system is part of the axotomy reaction and is suggested to modulate subsequent complement mediated effects.